Post-Hospital Availability of Instrumental Support May Influence Patients' Readiness for Discharge. Issue 4 (July 2022) - Schultz, Beth E.; Corbett, Cynthia F.; Hughes, Ronda G.; Bell, Nathaniel
Abstract : Purpose of Study: Evaluate the relationship between unplanned acute care utilization after discharge from an index hospital admission and registered nurse and patient perceptions of available instrumental support the patient would have after discharge. Primary Practice Setting: Three hospitals in a large regional hospital system in the southeastern United States. Methodology and Sample: Retrospective, secondary quantitative analysis of 13, 361 patient records (mean age 58.4 years; 51% female) from index hospitalizations evaluating patient and nurse responses to 2 questions that specifically address instrumental support on both the patient and nurse versions of the Readiness for Hospital Discharge Survey (RHDS) and subsequent unexpected care received (emergency department [ED] visit, observation stay, hospital readmission) in the acute care setting within 60 days of discharge. Logistic regression was used to evaluate the relationship between RHDS scores and unplanned care received. Results: Patients who required hospital-based acute care within 60 days after discharge had lower average RN-RHDS scores than those who did not require hospital-based acute care. Implications for Case Management Practice: Including a nursing assessment of potential postdischarge expected instrumental support may be helpful in identifying patients who are at a higher risk of experiencing postdischarge acute care utilization. Monitoring ED visits and observation stays in addition to readmissions will facilitate capturing significantly more points of care received after discharge and provide additional information regarding postdischarge care utilization.